New Evidence for Genome-Wide Duplications at the Origin of Vertebrates Using an Amphioxus Gene Set and Completed Animal Genomes - Panopoulou, Georgia; Hennig, Steffen; Groth, Detlef; Krause, Antje; Poustka, Albert J.; Herwig, Ralf; Vingron, Martin; Lehrach, Hans (Genome Research, 2003)
The 2R hypothesis predicting two genome duplications at the origin of vertebrates is highly controversial. Studies published so far include limited sequence data from organisms close to the hypothesized genome duplications. Through the comparison of a gene catalog from amphioxus, the closest living invertebrate relative of vertebrates, to 3453 single-copy genes orthologous between Caenorhabditis elegans (C), Drosophila melanogaster (D), and Saccharomyces cerevisiae (Y), and to Ciona intestinalis ESTs, mouse, and human genes, we show with a large number of genes that the gene duplication activity is significantly higher after the separation of amphioxus and the vertebrate lineages, which we estimate at 650 million years (Myr). The majority of human orthologs of 195 CDY groups that could be dated by the molecular clock appear to be duplicated between 300 and 680 Myr with a mean at 488 million years ago (Mya). We detected 485 duplicated chromosomal segments in the human genome containing CDY orthologs, 331 of which are found duplicated in the mouse genome and within regions syntenic between human and mouse, indicating that these were generated earlier than the human–mouse split. Model based calculations of the codon substitution rate of the human genes included in these segments agree with the molecular clock duplication time-scale prediction. Our results favor at least one large duplication event at the origin of vertebrates, followed by smaller scale duplication closer to the bird–mammalian split.